PRECOG: PREdicting COupling probabilities of G-protein coupled receptors - Singh, Gurdeep; Inoue, Asuka; Gutkind, J. Silvio; Russell, Robert B.; Raimondi, Francesco (Nucleic acids research, 2019)
Abstract. G-protein coupled receptors (GPCRs) control multiple physiological states by transducing a multitude of extracellular stimuli into the cell via coupl